The Military Art of the Great Warlord Jalaliddin Manguberdi in the Struggle Against Genghis Khan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article describes the brief life and activities of great warlord Jalaliddin Manguberdi, his bravery in front of our people, his unparalleled courage in the fight against the Mongol invaders, his loyalty and boundless love for the homeland and his people, his military activities, management system, and the supply of weapons.